Cathode active material with core-shell structure and manufacture thereof
Through the design of cathode active materials with a core-shell structure, the problems of insufficient specific capacity and resistance growth of existing materials are solved, the electrochemical performance is improved, and more efficient energy storage is achieved.
Patent Information
- Application Number
- CN202480016155.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-03
- Filing Date
- 2024-02-26
- Publication Date
- 2025-10-17
AI Technical Summary
Existing cathode active materials have problems in terms of electrochemical performance, such as insufficient specific capacity, resistance growth, and capacity loss caused by corrosion effects, and there is limited room for improvement in cobalt-coated materials.
A cathode active material with a core-shell structure is used, wherein the core material is polycrystalline Li1+xTM1-xO2, TM contains Ni, Mn, Co and Al, and the shell material is a cobalt compound and B or W oxide. The cobalt compound is enriched on the surface of the secondary particles to form an enrichment layer.
The specific capacity and cycle performance of the cathode active material are improved, the resistance growth is reduced, the conductivity is increased, and the capacity loss due to corrosion effects is avoided.
Smart Images

Figure BDA0005575607960000061 
Figure BDA0005575607960000062 
Figure BDA0005575607960000171
Abstract
Description
[0001] The present invention relates to a cathode active material, comprising
[0002] (A) a core material according to the general formula Li 1+x TM 1-x O2, wherein TM is a combination of at least two of Ni with Mn, Co and Al, and optionally at least one of a plurality of metals selected from the group consisting of Mg, Ti, Zr, Nb, Ta and W, and x is in the range of -0.05 to +0.05, and wherein the nickel content is in the range of 80 to 99 mol-% of TM, and
[0003] (B) particles of one or more cobalt compounds, wherein at least some of the cobalt is in the oxidation state of +III,
[0004] (C) a shell comprising an oxide of at least one of B or W,
[0005] wherein the core material (A) is a polycrystalline material, the secondary particles of the polycrystalline material are composed of primary particles, and the particles of the cobalt compound (B) are enriched at the surface of the secondary particles.
[0006] Lithium-ion secondary batteries are modern devices for storing energy. Many fields of application are already and are being considered, from small devices like mobile phones and laptops to car batteries and other batteries for electric cars. The various components of the battery like electrolyte, electrode materials and separators have a decisive influence on the performance of the battery. Particular attention is given to the cathode material. Several materials have been proposed, like lithium iron phosphate, lithium cobalt oxide and lithium nickel cobalt manganese oxide. Despite extensive research, the solutions found so far still leave room for improvement.
[0007] At present, a certain interest can be observed in so-called Ni-rich cathode active materials, for example cathode active materials containing 60 mol-% or more of Ni relative to the total content of metals other than lithium.
[0008] In US 6,921,609, a method for manufacturing cobalt-coated cathode active materials is disclosed. The disclosed cobalt-coated cathode active materials show an improved electrochemical behavior compared to the uncoated equivalent. However, the specific capacity leaves room for improvement.
[0009] It is an object of the present invention to provide cathode active materials with improved specific capacity and cycling performance, as well as reduced resistance growth. Furthermore, it is an object to increase the electrical conductivity and to avoid capacity loss due to corrosion effects.
[0010] Therefore, it has been found that the cathode active material defined at the outset, in the following also referred to as the cathode active material of the present invention. The cathode active material of the present invention is a particulate material, and it comprises
[0011] (A) a core material according to the general formula Li 1+x TM 1-x O2, wherein TM is a combination of Ni with at least two of Mn, Co and Al, and optionally at least one of a plurality of metals selected from Mg, Ti, Zr, Nb, Ta and W, and x is in the range of -0.05 to +0.05, and wherein the nickel content is in the range of 80 to 99 mol-% of TM, and
[0012] (B) particles of one or more cobalt compounds, wherein at least some cobalt is in the oxidation state of +III,
[0013] (C) a shell comprising an oxide of at least one of B or W,
[0014] wherein the core material (A) is a polycrystalline material, the secondary particles of which are composed of primary particles, and the particles of cobalt compounds (B) are enriched at the surface of said secondary particles.
[0015] The core material (A) and the particles (B) as well as the shell (C) will be described in more detail below.
[0016] In one embodiment of the present application, the core material (A) has an average particle size (D50) in the range of 3 to 20 pm, preferably 5 to 16 pm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles of the core material (A) are polycrystalline, which means that they are composed of a plurality of primary particles, and the above-mentioned particle size refers to the secondary particle size.
[0017] The shape of the primary particles is preferably platelet-like as detected by SEM / TEM imaging.
[0018] A plurality in the present context means several hundred or even more primary particles forming a secondary particle.
[0019] The core material (A) is preferably a nickel-rich cathode active material, which means that the molar percentage of nickel in the core material is at least 80 mol-%, for example 80 to 99 mol-%, relative to all metals in TM.
[0020] TM in the above formula contains at least one, preferably at least two, for example Co and Mn, or Co and Al, or even all three, i.e. Mn, Co and Al, of Mn, Co and Al.
[0021] Optionally, TM can contain at least one of a plurality of metals selected from Mg, Ti, Zr, Nb, Ta and W.
[0022] In one embodiment of the present application, TM is a combination of metals according to the general formula (I)
[0023] (Ni a Co b Mn c ) 1-d M d (I)
[0024] in
[0025] a is in the range of 0.80 to 0.99, preferably 0.83 to 0.95, more preferably 0.85 to 0.91,
[0026] b is in the range of 0.005 to 0.195, preferably 0.025 to 0.13, and more preferably 0.04 to 0.05,
[0027] c is in the range of 0.005 to 0.195, preferably 0.025 to 0.13, and more preferably 0.04 to 0.05,
[0028] d is in the range of 0 to 0.1, preferably 0,
[0029] M is selected from the group consisting of Al, Mg, Ti, Zr, Nb, Ta and W, and a combination of at least two of the foregoing, preferably Al and at least one of Al and the foregoing, and
[0030] a+b+c=1.
[0031] In another embodiment of the present invention, the variable TM corresponds to the general formula (Ia)
[0032] (Ni a* Co b *Al e* ) 1-d* M 2 d* (I a)
[0033] where a*+b*+e*=1, and
[0034] a* is in the range of 0.80 to 0.99, preferably 0.88 to 0.95,
[0035] b* is in the range of 0.005 to 0.19, preferably 0.025 to 0.1,
[0036] e* is in the range of 0.002 to 0.19, preferably 0.015 to 0.04,
[0037] d* is in the range of 0 to 0.1, preferably 0 to 0.02,
[0038] M 2 It is at least one of Mg, W, Mo, Ti or Zr.
[0039] In one embodiment of the application, TM corresponds to the general formula (I), and x1 is in the range of -0.05 to +0.05, preferably 0.01 to 0.05.
[0040] In one embodiment of the application, TM corresponds to the general formula (I a), and x1 is in the range of -0.05 to +0.05.
[0041] Some elements are ubiquitous. In the context of the present application, trace amounts of ubiquitous metals as impurities, such as sodium, calcium, iron or zinc, will not be considered in the description of the present application. Trace amounts will mean in the present context an amount of 0.05 mol-% or less, respectively, relative to the total metal content of TM or of particles (B).
[0042] Particles (B) comprise a lithium cobalt oxide compound, wherein at least some of the cobalt is in oxidation state +III, preferably most of the cobalt. The oxidation state of cobalt in particles (B) can be determined by X-ray photoelectron spectroscopy ("XPS"), and the position relative to core material (A) can be determined by imaging methods such as transmission electron microscopy ("TEM") and scanning electron microscopy ("SEM"). The phase type of particles (B) can be determined by high resolution X-ray powder diffraction ("XRD"). In a preferred embodiment, the average molar ratio of lithium to cobalt in particles (B) is in the range of 0 to below 1.
[0043] In one embodiment of the application, the average oxidation state of cobalt in particles (B) is in the range of +2 to +4, preferably above +2.5 to +3.5 and even more preferably +3.0.
[0044] The molar ratio of lithium to cobalt in particles (B) is in the range of 0 to 1, preferably above 0 to below 1, or it is 1 :1.
[0045] At least some of the cobalt in particles (B) is in oxidation state +III. This includes the option that all of the cobalt in particles (B) is in oxidation state +III, for example like in LiCoO2.
[0046] In one embodiment of the application, the cobalt in particles (B) is in the form of Li y1 CoO2(0 < y1 < 0.6), LiCoO2and LiCo y2 Ni 1-y2 O2(0.5 < y2 < 1).
[0047] In one embodiment, particles (B) are not composed of the defined compound, but of a mixture of several cobalt-containing oxides, for example, a substoichiometric lithium cobalt oxide compound, such as Li 0.5 CoO2in combination with LiCoO2.
[0048] More preferably, the particles mainly comprise LiCoO2, which can be detected by X-ray diffraction method ("XRD") using Cu radiation, Kα1 wavelength = 1.5406 A.
[0049] In the cathode active material of the present application, the particles (B) are enriched at the surface of the secondary particles. Preferably, no particles (B) migrate into the pores of the secondary particles.
[0050] In one embodiment of the present application, the weight ratio of the core material (A) to the particles (B) is in the range of 1000: 1 to 10 to 1, preferably 100: 1 to 20: 1.
[0051] In one embodiment of the present application, when implemented in a cathode in a full cell having a graphite anode, 20% to 45% of the secondary particles of the cathode active material of the present application exhibit cracks after 500 cycles of charge / discharge at 4.2-3.0 V at 40°C. Cracking is generally considered to be detrimental because a large number of cracks reduces the mechanical stability of the cathode, and cracks can reduce the migration of lithium ions.
[0052] In one embodiment of the present application, the particles (B) have an average diameter (D50) in the range of 10 nm to 10 pm, preferably 10 nm to 1 pm. The average diameter (D50) can be determined by measuring the average diameter of the particles (B) on the surface of the core material (A) using transmission electron microscopy ("TEM") or scanning electron microscopy ("SEM").
[0053] In one embodiment of the present application, the cathode active material of the present application further comprises one or more aluminum compounds and one or more titanium compounds or one or more zirconium compounds, each in the particles (B).
[0054] In one embodiment of the present application, the particles (B) comprise cobalt and lithium and Al and at least one of Ti and Zr as additional elements, and it is preferred that the particles (B) comprise more Co than any of Al, Ti and Zr. In embodiments where the particles (B) comprise Al and at least one additional element selected from Ti and Zr, the individual particles (B) can comprise both Li and Co and at least one of Ti, Zr and Al, but in other embodiments the individual particles comprise cobalt or any of Ti, Zr or Al.
[0055] However, preferably the particles (B) do not contain any of Al, Zr and Ti.
[0056] The particles of the cathode active material of the present application further comprise a shell (C). The shell (C) comprises an oxide of at least one of B or W, such as B2O3, WO3, LiBO2, Li2B4O7, or Li2WO4. In a preferred embodiment, the shell (C) contains at least 90% by weight of B2O3, WO3, Li2B4O7, Li2WO4, or LiBO2. More preferably, the shell (C) comprises an oxide of B, such as B2O3, LiBO2, or Li2B4O7, preferably at least 90% by weight.
[0057] In one embodiment of the present application, the shell (C) is glassy or amorphous and no crystalline phase can be detected by X-ray diffraction.
[0058] In one embodiment of the present application, the shell (C) is not a complete shell, but has holes comparable to Swiss cheese, such as a coverage of the outer surface of the secondary particles of 55% to 95%. In other embodiments, the shell (C) is not continuous, but shows an island-like structure.
[0059] In one embodiment of the present application, a majority of the particles of the cathode active material of the present application are coated to at least some extent, such as 90% to 99% of all particles, as determined by SEM / EDX imaging of a randomly chosen sample.
[0060] In one embodiment of the present application, the shell (C) has an average thickness in the range of 2 nm to 50 nm, preferably 5 nm to 30 nm, as detected by depth profiling XPS.
[0061] In one embodiment of the present application, the B- or W-containing glass phase fills into the grain boundaries between the primary particles to a depth of several micrometers, preferably less than 3 pm, as evidenced by depth profiling XPS.
[0062] In one embodiment of the present application, the cathode active material of the present application has a surface area (BET) in the range of 0.1 to 0.8 m 2 / g, as determined according to DIN-ISO 9277:2003-05.
[0063] Another aspect of the present application relates to electrodes comprising at least one electrode material active according to the present application. They are particularly useful for lithium ion batteries. Lithium ion batteries comprising at least one electrode according to the present application exhibit a good discharge behavior. Electrodes comprising at least one cathode active material according to the present application are also referred to as cathodes of the present application or cathodes according to the present application in the following.
[0064] The cathodes according to the present application can comprise additional components. They can comprise a current collector, such as, but not limited to, an aluminum foil. They can further comprise a conductive carbon and a binder.
[0065] Suitable binders are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free-radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene, and copolymers of at least two comonomers selected from the group consisting of ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. In addition, polyisoprene and polyacrylates are also suitable. Polyacrylonitrile is particularly preferred.
[0066] In the context of the present application, polyacrylonitrile is to be understood as meaning not only polyacrylonitrile homopolymers, but also copolymers of acrylonitrile with 1,3-butadiene or styrene. Polyacrylonitrile homopolymers are preferred.
[0067] In the context of the present application, polyethylene is to be understood as meaning not only homopolyethylene, but also copolymers of ethylene which comprise at least 50 mol% of copolymerized ethylene and up to 50 mol% of at least one further comonomer, for example an a-olefin such as propylene, butene (1 -butene), 1 -hexene, 1 -octene, 1 -decene, 1 -dodecene, 1 -pentene, and also isobutene, a vinyl aromatic compound such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C4-alkyl (meth)acrylates, maleic acid, maleic anhydride and itaconic anhydride. The polyethylene can be HDPE or LDPE. 10 - alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride. The polyethylene can be HDPE or LDPE.
[0068] In the context of the present application, polypropylene is to be understood as meaning not only homopolypropylene, but also copolymers of propylene which comprise at least 50 mol% of copolymerized propylene and up to 50 mol% of at least one further comonomer, for example ethylene and an a-olefin such as butene, 1 -hexene, 1 -octene, 1 -decene, 1 -dodecene and 1 -pentene. The polypropylene is preferably isotactic or substantially isotactic.
[0069] In the context of the present application, polystyrene is to be understood as meaning not only homopolymers of styrene, but also copolymers with acrylonitrile, 1,3-butadiene, (meth)acrylic acid, C1-C4-alkyl (meth)acrylates, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenyl ethylene and a-methylstyrene. 10 - alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride. The polyethylene can be HDPE or LDPE.
[0070] Another preferred binder is polybutadiene.
[0071] Other suitable binders are selected from the group consisting of polyethylene oxide (PEO), cellulose, carboxymethylcellulose, polyimide and polyvinyl alcohol.
[0072] In one embodiment of the present application, the binder is selected from those (co)polymers having an average molecular weight Mw in the range of 50,000 to 1,000,000 g / mol, preferably to 500,000 g / mol. w
[0073] The binder can be a cross-linked or non-cross-linked (co)polymer.
[0074] In a particularly preferred embodiment of the present application, the binder is selected from halogenated (co)polymers, especially from fluorinated (co)polymers. Halogenated or fluorinated (co)polymers are to be understood to mean those (co)polymers which comprise at least one (co)monomer which has at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule. Examples are polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and ethylene-chlorofluoroethylene copolymer.
[0075] Suitable binders are especially polyvinyl alcohol and halogenated (co)polymers, such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.
[0076] The cathode of the present application can comprise 1 % to 15 % by weight of one or more binders relative to the cathode active material. In other embodiments, the cathode of the present application can comprise 0.1 % to less than 1 % by weight of one or more binders.
[0077] A further aspect of the present application is a battery comprising at least one cathode comprising the cathode active material of the present application, carbon, and a binder, at least one anode, and at least one electrolyte.
[0078] Embodiments of the cathode of the present application have been described in detail above.
[0079] The anode can contain at least one anode active material, such as carbon (graphite), Ti02, lithium titanium oxide, silicon or tin. The anode can additionally contain a current collector, such as a metal foil, such as a copper foil.
[0080] The electrolyte can comprise at least one non-aqueous solvent, at least one electrolyte salt and optionally additives.
[0081] The nonaqueous solvent of the electrolyte can be liquid or solid at room temperature and is preferably selected from the group consisting of polymers, cyclic or acyclic ethers, cyclic or acyclic acetals and cyclic or acyclic organic carbonates.
[0082] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-Ci-C4-alkylene glycols, and in particular polyethylene glycols. Here, the polyethylene glycol can comprise up to 20 mol% of one or more Ci-C4-alkylene glycols. The polyalkylene glycol is preferably a polyalkylene glycol which is terminated on both sides by a methyl or ethyl group.
[0083] The molecular weight M of the suitable polyalkylene glycol and in particular of the suitable polyethylene glycol can be at least 400 g / mol. w The molecular weight M of the suitable polyalkylene glycol and in particular of the suitable polyethylene glycol can be at least 400 g / mol.
[0084] The molecular weight M of the suitable polyalkylene glycol and in particular of the suitable polyethylene glycol can be at least 400 g / mol. w The molecular weight M of the suitable polyalkylene glycol and in particular of the suitable polyethylene glycol can be at least 400 g / mol.
[0085] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, of which 1,2-dimethoxyethane is preferred.
[0086] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.
[0087] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1 -dimethoxyethane and 1,1 -diethoxyethane.
[0088] Examples of suitable cyclic acetals are 1,3-dioxane and in particular 1,3-dioxolane.
[0089] Examples of suitable acyclic organic carbonates are dimethyl carbonate, methyl ethyl carbonate and diethyl carbonate.
[0090] Examples of suitable cyclic organic carbonates are compounds according to the general formulae (II) and (III)
[0091]
[0092] wherein R 1 , R 2 and R 3 may be identical or different and are selected from the group consisting of hydrogen and Ci-C4-alkyl, for example methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, sec-butyl and t-butyl, wherein R 2 and R 3 are preferably not both t-butyl.
[0093] In particularly preferred embodiments, R 1 is methyl and R 2 and R 3 are each hydrogen, or R 1 , R 2 and R 3 are each hydrogen.
[0094] Another preferred cyclic organic carbonate is vinylene carbonate, formula (IV).
[0095]
[0096] The solvent or solvents are preferably used in anhydrous state, i.e. with a water content in the range of 1 ppm to 0.1 % by weight, which can be determined, for example, by Karl-Fischer titration.
[0097] The electrolyte (C) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiCIO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imides such as LiN(C n F 2n+1 SO2)2, wherein n is an integer in the range of 1 to 20, LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and salts of the general formula (C n F 2n+1 SO2) t YLi, wherein m is defined as follows:
[0098] when Y is selected from oxygen and sulfur, t = 1,
[0099] when Y is selected from nitrogen and phosphorus, t = 2, and
[0100] when Y is selected from carbon and silicon, t = 3.
[0101] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiCIO4, wherein LiPF6 and LiN(CF3SO2)2 are particularly preferred.
[0102] In embodiments of the application, the battery according to the application comprises one or more separators by means of which the electrodes are mechanically separated. Suitable separators are polymeric films, in particular porous polymeric films, which are non-reactive towards metallic lithium. Materials which are particularly suitable for use in separators are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.
[0103] The separator consisting of a polyolefin, in particular polyethylene or polypropylene, can have a porosity in the range of 35 to 45 %. Suitable pore sizes are for example in the range of 30 to 500 nm.
[0104] In another embodiment of the present application, the separator can be selected from PET nonwoven materials filled with inorganic particles. Such separators can have a porosity in the range of 40 to 55 %. Suitable pore sizes are for example in the range of 80 to 750 nm.
[0105] The battery according to the present application further comprises a housing, which can have any shape, for example the shape of a cuboid or a cylindrical disc or a cylindrical can. In one variant, a metal foil configured as a pouch is used as a housing.
[0106] The battery according to the present application shows a good discharge behavior, for example a very good discharge and cycling behavior at low temperatures (0 °C or less, for example down to -10 °C or even less).
[0107] The battery according to the present application can comprise two or more electrochemical cells combined with each other, which can for example be connected in series or in parallel. A connection in series is preferred. In the battery according to the present application, at least one of the electrochemical cells comprises at least one cathode according to the present application. Preferably, in the electrochemical cells according to the present application, the majority of the electrochemical cells comprises a cathode according to the present application. Even more preferably, in the battery according to the present application, all electrochemical cells comprise a cathode according to the present application.
[0108] The present application further relates to the use of a battery according to the present application in a device, in particular in a mobile device. Examples of mobile devices are vehicles, for example cars, bicycles, aircraft or water vehicles (such as ships or vessels). Other examples of mobile devices are those which are moved manually, for example computers (especially laptops), telephones, or electric hand tools (for example in the construction industry), in particular drills, battery-powered screwdrivers or battery-powered staplers.
[0109] The present application further relates to a process for manufacturing the cathode active material of the present application, in the following also referred to as "process of the present application" or "process according to the present invention".
[0110] The process of the present application comprises at least five steps: (a), (b), (c), (d) and (e), in the context of the present application also referred to as step (a) and step (b) and step (c) and step (d) and step (e), respectively. Steps (a) and (b) and (d) and (e) are performed subsequently. Steps (b) and (c) can be performed consecutively or simultaneously.
[0111] The method of the present invention comprises the following steps
[0112] (a) providing an oxide or (oxy)hydroxide of TM, wherein TM is a combination of Ni and at least two of Mn, Co and Al, and optionally at least one metal selected from Mg, Ti, Zr, Nb, Ta and W, and wherein the nickel content is in the range of 80 to 99 mol-% of TM,
[0113] (b) mixing said oxide or (oxy)hydroxide with an oxide or (oxy)hydroxide of cobalt and optionally at least one oxide or (oxy)hydroxide of Al, Nb, Ti or Zr, thereby obtaining a premix,
[0114] (c) adding a lithium source to the premix obtained in step (b) at a molar ratio of Li to TM in the range of (1+x+y) / (1-x), wherein x is in the range of 0 to 0.05, and y is in the range of 0 to 0.1, thereby obtaining a mixture, and
[0115] (d) calcining the mixture of step (c),
[0116] (e) at least one post-processing step selected from the group consisting of
[0117] (e1) treating the calcined material from step (d) with water, followed by a liquid-solid separation step, and
[0118] (e2) Adding a compound of W or preferably B to the calcined material of step (d) or to the treated material from step (e1 ) and performing a heat treatment at a temperature in the range of 250°C to 400°C.
[0119] Steps (a) to (e) will be explained in more detail below.
[0120] The method of the present invention begins with a precursor for the cathode active material. This precursor is an oxide or (oxy)hydroxide of TM, wherein TM is a combination of Ni and at least two of Mn, Co, and Al, and optionally at least one metal selected from Mg, Ti, Zr, Nb, Ta, and W, and wherein the nickel content is in the range of 80 to 99 mol% of TM. The precursor may also be referred to as the "starting material" hereinafter.
[0121] In one embodiment of the present invention, the starting material has an average particle size (D50) in the range of 3 to 20 μm, preferably 5 to 16 μm. The average particle size can be determined, for example, by light scattering, laser diffraction, or electroacoustic spectroscopy. The particles are typically composed of agglomerates of primary particles, and the above particle sizes refer to secondary particle sizes.
[0122] In one embodiment of the present application, the starting material has a monomodal particle size distribution. In another embodiment of the present application, the starting material has a bimodal particle size distribution.
[0123] In one embodiment of the present application, the starting material has a narrow span of the particle size distribution. The span can be expressed as (D90-D10) / (D50), and D90 and D10 are the corresponding percentile values.
[0124] In one embodiment of the present application, when (oxy)hydroxide is used as the starting material, the starting material has a specific surface area (BET), hereinafter also referred to as "BET surface area", in the range of 3 to 50 m2 / g. The BET surface area can be determined according to DIN ISO 9277:2010 by nitrogen adsorption after degassing the sample at 120 °C for 30 minutes or more and beyond this time. 2
[0125] In one embodiment of the present application, when oxide is used as the starting material, the starting material has a BET surface area in the range of 50 to 250 m2 / g. The BET surface area can be determined according to DIN ISO 9277:2010 by nitrogen adsorption after degassing the sample at 120 °C for 30 minutes or more and beyond this time. 2
[0126] In one embodiment of the present application, in step (a), an oxide of TM having a moisture content in the range of 0 to 100 ppm, preferably 1 to 50 ppm, determined by Karl-Fischer titration is provided. In the present context, 0 means "below the detection level".
[0127] The core material (A) is preferably a nickel-rich cathode active material. Although the percentage of nickel in the core material can be 50 mole-% or even lower, e.g. 40 mole-%, it is preferred that the mole percentage of nickel in the core material is at least 60 mole-% relative to all metals in the TM.
[0128] TM in the above formula contains at least one, preferably at least two, of Mn, Co and Al, e.g. Co and Mn, Co and Al, or even Mn, Co and Al.
[0129] Optionally, TM can contain at least one of a plurality of metals selected from the group consisting of Mg, Ti, Zr, Nb, Ta and W.
[0130] In one embodiment of the present application, TM is a combination of metals according to general formula (I)
[0131] (Ni a Co b Mn c ) 1-d M d (I)
[0132] wherein
[0133] a is in the range of 0.80 to 0.99, preferably 0.83 to 0.95, more preferably 0.85 to 0.91,
[0134] b is in the range of 0.005 to 0.195, preferably 0.025 to 0.13, and more preferably 0.04 to 0.05,
[0135] c is in the range of 0.005 to 0.195, preferably 0.025 to 0.13, and more preferably 0.04 to 0.05,
[0136] d is in the range of 0 to 0.1, preferably 0,
[0137] a + b + c = 1.
[0138] In another embodiment of the present application, the variable TM corresponds to the general formula (I a)
[0139] (Ni a* Co b *Al e* ) 1-d* M 2 d* (I a)
[0140] wherein a* + b* + e* = 1, and
[0141] a* is in the range of 0.80 to 0.99, preferably 0.88 to 0.95,
[0142] b* is in the range of 0.005 to 0.19, preferably 0.025 to 0.1,
[0143] e* is in the range of 0.002 to 0.19, preferably 0.015 to 0.04,
[0144] d* is in the range of 0 to 0.1, preferably 0 to 0.02,
[0145] M 2 is at least one of Mg, W, Mo, Ti or Zr.
[0146] The starting material provided in step (a) is typically free of conductive carbon, which means that the conductive carbon content of the starting material is less than 1% by weight, preferably in the range of 0.001% to 1.0% by weight, relative to said starting material.
[0147] The starting material provided in step (a) is typically free of lithium. This means that the lithium content in the starting material provided in step (a) is below 0.1 % by weight relative to the starting material, preferably in the range of 0 to 100 ppm. Lithium compounds in the starting material are typically impurities.
[0148] However, some elements are ubiquitous. In the context of the present invention, trace amounts of ubiquitous metals as sodium, calcium, iron or zinc as impurities are not to be considered. Trace amounts in the present context are to mean amounts of 0.05 mol-% or less relative to the total metal content of the starting material.
[0149] In step (b), the starting material is contacted with an oxide or (oxy)hydroxide of cobalt and, optionally, up to 10% by volume of water and, optionally, at least one oxide or hydroxide or oxyhydroxide of Ti, Zr or Al or Nb, wherein the oxide or (oxy)hydroxide of cobalt has an average particle size (D50) in the range of 10 nm to 50 pm and a particle size distribution span in the range of 0.5 to 3.5, followed by mixing.
[0150] Examples of oxides and hydroxides of cobalt are CoO, Co3O4, Co(OH)2, CoOOH and non-stoichiometric oxyhydroxides of cobalt. Preferred are Co(OH)2and Co3O4.
[0151] Examples of optionally added oxides or hydroxides or oxyhydroxides of Ti, Zr, Nb or Al are TiO2, Ti2O3, TiO(OH)2, TiO2aqueous solution, Al2O3, AlOOH, Al(OH)3, Al2O3aqueous solution, ZrO2, Zr(OH)4and ZrO2aqueous solution and Nb2O5and Nb2O5aqueous solution (“niobium acid”).
[0152] Step (b) can be performed by mixing the respective components in a mixer, for example in a high shear mixer. For laboratory scale experiments, also ball mills and roller mills can be applied.
[0153] In one embodiment of the present invention, the molar ratio of cobalt added in step (b) is in the range of 0.5% to 5%, preferably 1% to 3%, of TM.
[0154] Step (b) can be performed with the addition of water or organic solvents, but it is preferred that no organic solvent or water is added in substep (b) or in any of the substeps.
[0155] The preferred duration of step (b) is in the range of 1 to 60 minutes.
[0156] In one embodiment of the present application, step (b) is performed by charging the vessel with the starting materials provided in step (a) and adding an oxide or (oxy)hydroxide of cobalt.
[0157] In step (b) a premix is obtained.
[0158] Step (c) comprises adding a lithium source to the premix obtained in step (b) in a molar ratio of Li to TM in the range of (1 + x + y) / (1 - x), wherein x is in the range of 0 to 0.05 and y is in the range of 0 to 0.1, thereby obtaining a mixture. Suitable lithium sources are LiOH (with or without hydrate), Li2CO3 and Li2O2 and mixtures of at least two of the foregoing, such as a mixture of LiOH and Li2O2.
[0159] Step (c) can be performed in the same vessel as step (b).
[0160] Step (d) comprises calcining the mixture obtained from step (b), for example at a temperature in the range of 550 °C to 800 °C, preferably 575 °C to 775 °C.
[0161] Step (d) can be performed in any type of oven, such as a roller hearth kiln, a pusher kiln, a rotary kiln, a pendulum kiln, or a muffle oven for laboratory scale experiments.
[0162] The temperature of 550 °C to 800 °C corresponds to the maximum temperature of step (d).
[0163] The mixture obtained from step (c) can be subjected directly to step (d). However, it is preferred to gradually increase the temperature, or to ramp the temperature. Said gradual increase or ramping can be performed at normal pressure or at reduced pressure, for example 1 to 500 mbar.
[0164] Step (d) - at its maximum temperature - can be performed at normal pressure.
[0165] Step (d) is performed under an oxygen-containing atmosphere, either oxygen-enriched air with at least 80 vol-% oxygen, or under pure oxygen.
[0166] In one embodiment of the present application, step (d) is performed under an atmosphere with a reduced CO2 content, for example a carbon dioxide content in the range of 0.01 to 500 ppm by weight, preferably 0.1 to 50 ppm by weight. The CO2 content can be determined by optical methods, for example using infrared light. It is even more preferred to perform step (d) under an atmosphere with a carbon dioxide content below the detection limit, for example with optical methods based on infrared light.
[0167] In one embodiment of the present invention, step (d) is carried out in a roller-hearth kiln, a pusher kiln, a rotary kiln, or a combination of at least two of the foregoing. The advantage of a rotary kiln is that the homogeneity of the material produced therein is excellent. In roller-hearth and pusher kilns, different reaction conditions for the different steps can be easily set. For laboratory-scale experiments, box and tube furnaces, as well as split-tube furnaces, are also feasible.
[0168] In one embodiment of the present invention, step (d) of the present invention is carried out under a forced gas flow (e.g., air, oxygen, and oxygen-enriched air). Such a gas flow may be referred to as a forced gas flow. Such a gas flow may have a flow rate of 0.5 to 15 m / s. 3 The specific flow rate is in the range of 1 / h·kg of the mixture from step (c). The volume is measured under the following standard conditions: 298 Kelvin and 1 atmosphere. The forced gas flow can be used to remove gaseous cracking products such as water.
[0169] In one embodiment of the invention, step (d) has a duration in the range of 2 to 30 hours, preferably 6 to 24 hours. In this context, the cooling time is ignored.
[0170] The method of the present invention comprises a post-treatment step selected from steps (e1) and (e2), namely
[0171] step (e1) of treating the material obtained from step (d) with an aqueous medium, preferably water, followed by a liquid-solid separation step, and / or
[0172] A compound of tungsten or preferably boron is added to the material obtained from step (d) or (e1), respectively, and a subsequent heat treatment step (e2).
[0173] More preferably, the method of the present invention comprises both steps (e1) and (e2). Steps (e1) and (e2) are described in more detail below.
[0174] In the optional step (e1), the cathode active material obtained from step (d) is treated with an aqueous medium, preferably water or an aqueous solution of LiOH. The aqueous medium may have a pH value in the range of 7 to 14, preferably at least 3.5, more preferably 5 to 7 or 10 to 13. The pH value is measured at the beginning of step (e1). It is observed that during the process of step (e1), the pH value increases to at least 10, for example 11 to 13. In embodiments where the pH value is in the range of 10 to 11 at the beginning of step (e1), the value increases to greater than 11 up to 13. In embodiments where the pH value is in the range of 3 to less than 10 at the beginning of step (e1), the value increases to 11 up to 13 during the process of step (e1).
[0175] Preferably the water hardness of the aqueous medium used in step (e1 ) is at least partially removed, in particular calcium. Preferably demineralized water is used.
[0176] The pH value of the aqueous medium is influenced by substances dissolved or slurried in the aqueous medium, for example acidic compounds such as sulfuric acid or aluminum sulfate, or bases such as LiOH or NaOH. In a preferred embodiment, such aqueous medium is water.
[0177] In one embodiment of the present application, step (e1 ) is carried out at a temperature in the range of 5°C to 85°C, preferably 5°C to 30°C.
[0178] In one embodiment of the present application, step (e1 ) is carried out at normal pressure. But preferably step (e1 ) is carried out at elevated pressure (for example at 10 mbar to 10 bar above normal pressure) or with suction (for example 50 to 250 mbar below normal pressure, preferably 100 to 200 mbar below normal pressure).
[0179] Step (e1 ) can for example be carried out in a vessel which can be easily drained for example due to its position above a filter device. The material from step (d) can be charged into such vessel, followed by the aqueous medium. In another embodiment, the aqueous medium is charged into such vessel, followed by the material from step (d). In another embodiment, the material from step (d) and the aqueous medium are introduced simultaneously.
[0180] In one embodiment of the present application, in step (e1 ) the amounts of water and electrode active material have a weight ratio in the range of 1 :5 to 5:1, preferably 2:1 to 1 :2.
[0181] Step (e1 ) can be supported by mixing action (for example shaking) or in particular by stirring or shearing, see below.
[0182] In one embodiment of the present application, step (e1 ) has a duration in the range of 1 minute to 90 minutes, preferably 1 minute to less than 60 minutes. In embodiments where in step (e1 ) water treatment and water removal are carried out overlapping or simultaneously, a duration of 5 minutes or more is possible.
[0183] In one embodiment of the present application, the treatment according to step (e1 ) and the removal of the aqueous medium are carried out continuously.
[0184] After or during the treatment with the aqueous medium according to step (e1 ), water can be removed by any type of filtration (for example on a belt filter or in a filter press).
[0185] In one embodiment of the present application, the removal of the aqueous medium is started at the latest 5 minutes after starting step (e1 ). Such removal comprises a partial removal of water from the treated particulate electrode active material, for example by solid-liquid separation, for example by decanting or preferably by filtration. Said "partial removal" can also be referred to as partial separation.
[0186] In one embodiment of the present application, the slurry obtained in step (e1 ) is directly discharged into a centrifuge, for example a decanting centrifuge or a filtering centrifuge, or onto a filtration device, for example onto a suction filter or into a filter press or into a belt filter, which is preferably directly located below the vessel in which step (b) is carried out. Then, the filtration is started.
[0187] In a particularly preferred embodiment of the present application, step (e1 ) and the removal of the aqueous medium are carried out in a filter press or in a filtration device with stirrer, for example a pressure filter with stirrer or a suction filter with stirrer (German for example "Rührfilternutsche"). The removal of the aqueous medium is started at the latest 5 minutes, preferably at the latest 3 minutes, or even immediately after combining the starting materials and the aqueous medium according to step (e1 ). On a laboratory scale, the treatment with the aqueous medium and the removal of the aqueous medium can be carried out on a Buchner funnel assisted by manual stirring.
[0188] In a preferred embodiment, step (e1 ) is carried out in a filtration device, for example a filtration device which allows for stirring of the slurry or the filter cake in the filter.
[0189] In one embodiment of the present application, the removal of the aqueous medium or water according to step (e1 ) has a duration in the range of 1 minute to 1 hour.
[0190] In one embodiment of the present application, the stirring in step (e1 ) is carried out at a rate in the range of 1 to 50 revolutions per minute ("rpm"), preferably 5 to 20 rpm. In other embodiments, the rate is 200 to 400 rpm.
[0191] In one embodiment of the present application, the filtration medium can be selected from the group consisting of ceramics, sintered glass, sintered metal, organic polymer membranes, nonwoven materials, and fabrics.
[0192] In one embodiment of the present application, step (e1 ) is carried out under an atmosphere with a reduced CO2 content, for example a carbon dioxide content in the range of 0.01 to 500 ppm by weight, preferably 0.1 to 50 ppm by weight. The CO2 content can be determined by optical methods, for example using infrared light. It is even more preferred to carry out step (e1 ) under an atmosphere with a carbon dioxide content below the detection limit, for example with an optical method based on infrared light.
[0193] A solid residue, preferably in the form of a wet cake, is obtained from step (el). The moisture content of the solid residue and especially of the cake can be in the range of 3 to 20% by weight, preferably 4 to 9% by weight.
[0194] After step (el), drying can be performed, for example under nitrogen or under reduced pressure ("in vacuum"), at 50 to 150°C, to obtain a free-flowing powder.
[0195] Step (e2) comprises adding a compound of B or W, preferably a compound of boron, respectively, to the calcined mixture of step (d) or to the material obtained from step (el) and performing a heat treatment at a temperature in the range of 250 to 400°C.
[0196] Examples of compounds of tungsten are WO3, (NH4)2WO4, Li2WO4and Li4WO5.
[0197] Examples of compounds of boron are B2O3, boric acid (B(OH)3) and lithium borate, for example LiBO2. Preferably boric acid. The compound of boron can be added in bulk or in solution form, for example as an aqueous solution.
[0198] A combination of compounds of tungsten and boron is also possible.
[0199] In a preferred embodiment, step (e2) is performed as indicated above, but without drying, and the compound of boron is added to the slightly wet or even wet cake.
[0200] In one embodiment of the present application, the material obtained from step (d) is allowed to interact with each other, for example in the range of 10 minutes to 5 hours and at a temperature of 5 to 85°C.
[0201] In one embodiment of the present application, the amount of the compound of tungsten or preferably boron added in step (e2) is in the range of 0.05 to 1.5 mol-%, preferably 0.15 to 0.9 mol-%, relative to TM.
[0202] After addition of the compound of tungsten or boron, a heat treatment is performed. The heat treatment can be performed in any type of oven, for example roller hearth, pusher, rotary, suspension bell, or for laboratory scale experiments a muffle oven.
[0203] The temperature of the heat treatment in step (e2) can be in the range of 250 to 400°C. The temperature refers to the maximum temperature of step (e2).
[0204] In one embodiment of the present invention, the temperature is ramped up and then reaches the desired temperature of 250° C. to 400° C. For example, the mixture of step (e2) is first heated to a temperature of 250° C. to 300° C. and then kept constant for a period of 10 min to 4 hours, and then it is increased to 325° C. to 400° C.
[0205] In one embodiment of the present invention, the heating rate in step (e2) is in the range of 0.1 to 10°C / min.
[0206] In one embodiment of the present invention, the heat treatment step (e2) is carried out in a roller-hearth kiln, a pusher kiln, a rotary kiln, or a combination of at least two of the foregoing. A rotary kiln has the advantage that the homogeneity of the material produced therein is very good. In roller-hearth kilns and pusher kilns, different reaction conditions for the different steps can be easily set. For laboratory-scale experiments, box-type and tube furnaces, as well as split-tube furnaces, are also feasible.
[0207] In one embodiment of the invention, the heat treatment in step (e2) is carried out in an oxygen-containing atmosphere, for example, in a nitrogen-air mixture, in a rare gas-oxygen mixture, in air, in oxygen, or in an oxygen-enriched air or in pure oxygen. In a preferred embodiment, the atmosphere in step (e2) is selected from air, oxygen, and oxygen-enriched air. Oxygen-enriched air can, for example, be a 50:50 mixture by volume of air and oxygen. Other options are a 1:2 mixture by volume of air and oxygen, a 1:3 mixture by volume of air and oxygen, a 2:1 mixture by volume of air and oxygen, and a 3:1 mixture by volume of air and oxygen. Pure oxygen is even more preferred.
[0208] In one embodiment of the invention, the heat treatment in step (e2) has a duration in the range of 30 minutes to 5 hours. Preferably, it is 60 minutes to 4 hours. In this context, the cooling time is ignored.
[0209] The present invention is further illustrated by working examples.
[0210] Overview:
[0211] Particle cracking is measured as follows:
[0212] (1) training artificial intelligence ("AI") to recognize polished cross-sections of particles of cathode active material and to ignore subsurface features of particles of cathode active material;
[0213] (2) Only the outer perimeter of the cathode active material particles is tracked because they are in contact with the electrolyte, ignoring the internal voids that should not be in contact with the electrolyte;
[0214] (3) determining the polished cross-sectional area of the cathode active material particles;
[0215] (4) The total perimeter divided by the polished cross-sectional area (for normalization purposes), and used as a quantifiable measure of cracking. That is, the higher the P / A ratio, the more extensive the cracking of the cathode active material.
[0216] I. Cathode active material
[0217] I.1. Preparation of the precursor, step (a.1)
[0218] The stirred tank reactor was first filled with deionized water to which ammonium sulfate was added (49 g / kg water). The solution was controlled to 55°C and the pH value was controlled to 12 by adding aqueous sodium hydroxide solution.
[0219] The tank reactor was simultaneously fed with aqueous transition metal sulfate solution and aqueous sodium hydroxide solution at a flow rate ratio of 1.8 and a total flow rate resulting in a residence time of 8 hours. The aqueous transition metal sulfate solution comprised Ni, Co, Mn in a molar ratio of 91 : 4.5 : 4.5 and a total transition metal concentration of 1.45 mol / kg. The aqueous sodium hydroxide solution was a mixture of sodium hydroxide solution (50 wt.%) and ammonia solution (30 wt.%) in a weight ratio of 6. The pH value of 12 was maintained by separate feeding of the aqueous sodium hydroxide solution. The mother liquor was continuously removed starting from the start of all feedings. All feed streams were stopped after 27 hours. The resulting suspension was obtained by filtration, washed with distilled water, dried at 120°C in air and sieved to obtain the mixed transition metal (TM) oxyhydroxide precursor TM-OH.1.
[0220] The so obtained oxyhydroxide precursor TM-OH.1 was then calcined at 475°C to yield the oxide precursor TM-O.1.
[0221] I.2. Preparation of the cathode active material (raw), steps (b.1) to (d.1)
[0222] The oxide precursor TM-O.1 was mixed with 1.0 mole-% Co(OH)2, 1.6 mole-% Al(OH)3 and 0.3 mole-% ZrO2, all mole-% relative to the sum of Ni, Co and Mn in TM-O.1, and LiOH monohydrate in a Li / TM molar ratio of 1.03. The mixture was heated to 765°C for 8 hours in a forced oxygen stream to obtain the cathode active material B-CAM.1.
[0223] In a comparative sample, the same mixture was prepared except that no Co(OH)2 was added. After calcination of the mixture, the comparative cathode active material C-B.CAM.2 was obtained.
[0224] D50 = 12.6 pm was measured using laser diffraction technique in a Mastersizer 3000 instrument from Malvern Instruments. Residual moisture 136 ppm was determined at 230 °C.
[0225] I.3. Work-up process
[0226] I.3.1. Washing step (e1.1)
[0227] The cathode active material according to I.2. was poured into deionized water and stirred for 5 min at ambient temperature. The ratio of B-CAM.1- or C-B-CAM.2- to water was 2000 g / L. The resulting slurry was filtered and the washed cathode active material CAM.W.1(2) was obtained by filtration and dried at 120 °C in air.
[0228] I.3.2. Coating step (e2.1)
[0229] The washed cathode active material CAM.W.1(2) obtained according to I.3.1. was mixed with 0.9 mole-% H3BO3 in a roll mill. Mole-% relative to the sum of Ni, Co and Mn in CAM.W.1(2). The resulting mixture was then heated at 300 °C for 5 h in a forced oxygen flow to obtain the cathode active material CAM.1 or C-CAM.2, respectively.
[0230] SEM / EDX analysis showed sub-micron sized coated particles (D50 = 100-500 nm) of the Co compound (B.1) which were island-like enriched on the surface of the CAM.1 particles. TEM / EDX mapping of particle cross-sections confirmed no Co enrichment at the grain boundaries of the primary particles. Surface sensitive XPS showed the formation of a boron shell (C) containing LiBO2 and Li2B4O7 phases at the surface of the secondary particles of CAM.1 and C-CAM.2 and depth profiling XPS showed a boron coating depth of several micrometers along the grain boundaries of the primary particles.
[0231] A synchrotron source X-ray diffractometer (ALBA synchrotron light source, BL04-MSPD, Spain) was used for high resolution X-ray diffraction. Rietveld refinement using the XRD pattern of CAM.1 showed the formation of LiCoO2 with a layered crystal structure.
[0232] I.4 Further examples
[0233] The protocol of I.1 to I.3 was repeated, but the amounts of LiOH, Co(OH)2, Al(OH)3, ZrO2, H3BO3 and WO3 are shown in Table 1.
[0234] Table 1: Data for additional cathode active materials - Inventive and Comparative
[0235] CAM Li / M Co (mol%) Al (mol%) Zr (mol%) W (mol-%) B (mol-%) CAM.3 1.02 1.0 1.0 0.3 0.03 0 C-CAM.4 1.02 0 1.0 0.3 0.03 0 CAM.5 1.02 1.0 1.0 0.3 0 0.9 C-CAM.6 1.02 0 1.0 0.3 0 0.9 CAM.7 1.02 1.0 1.0 0.3 0.015 0.45 C-CAM.8 1.02 0 1.0 0.3 0.015 0.45
[0236] II. Testing of cathode active materials
[0237] II.1. Electrode Preparation, General Procedure
[0238] II.1.1. Cathode preparation
[0239] PVDF adhesive ( 5130) was dissolved in NMP (Merck) to produce a 7.5 wt.% solution. For the preparation of the electrodes, a binder solution (3 wt.%), graphite (SFG6L, 2 wt.%) and carbon black (Super C65, 1 wt.%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp., Japan), CAM.1 of the present invention or comparative cathode active material C-CAM (94 wt.%) was added and the suspension was mixed again to obtain a lump-free slurry. The solid content of the slurry was adjusted to 65%. The slurry was coated onto Al foil using a roll-to-roll coater. All electrodes were calendered before use. The thickness of the cathode material was 70 μm, corresponding to 15 mg / cm2. All electrodes were dried at 105°C for 7 hours before battery assembly.
[0240] II.1.2. Fabrication of Pouch Cell Anodes
[0241] Graphite and carbon black are thoroughly mixed. CMC (carboxymethyl cellulose) aqueous solution and SBR (styrene butadiene rubber) aqueous solution are used as binders. A mixture of graphite and carbon black (weight ratio of cathode active material: carbon: CMC: SBR = 96:0.5:2:1.5) is mixed with a binder solution and sufficient water to prepare a suitable slurry for electrode preparation. Therefore, the obtained slurry is applied to a copper foil (thickness = 10 μm) using a roller coater and dried at ambient temperature. For the single-layer pouch cell test, the sample loading was fixed at 10 mg / cm2.
[0242] II.2. Electrolyte Preparation
[0243] The base electrolyte was prepared by mixing 12.7 wt.% LiPF6, 26.2 wt.% ethylene carbonate (EC), and 61.1 wt.% ethyl methyl carbonate (EMC) (EL Base 1), based on the total weight of EL Base 1. To this base electrolyte formulation, 2 wt.% vinylene carbonate (VC) was added (EL Base 2).
[0244] II.3. Testing of battery cells
[0245] II.3.1. Button-type half battery cell
[0246] Button-type half battery cells (20 mm in diameter and 3.2 mm in thickness) comprising a cathode as prepared under II.1.1 and lithium metal as working and counter electrode, respectively, were assembled in an Ar-filled glovebox. The cathode, anode and separator were stacked in the order cathode / / separator / / Li foil to produce the half button battery cell. Thereafter, 0.15 mL of EL matrix 1 as described under II.2. was added to the button battery cell.
[0247] II.3.2. Pouch battery cell
[0248] Single layer pouch battery cells (70 mA h) comprising anodes as prepared under II.1.1. and graphite anodes according to II.1.2. were assembled and encapsulated in an Ar-filled glovebox. The cathode and anode and separator were stacked in the order cathode / / separator / / anode to produce the single layer pouch battery cell. Thereafter, 0.8 mL of EL matrix 2 electrolyte was introduced into the laminated pouch battery cell.
[0249] III. Evaluation of battery cell performance
[0250] III.1. Evaluation of button half battery cell performance
[0251] Battery cell performance was evaluated using the produced button-type half battery cells. Initial capacity and capacity retention measurements were as follows.
[0252] Button-type half battery cells according to II.3.1. were tested at room temperature over a voltage range between 4.3 and 2.7 C. For the initial cycle, delithiation was performed in CC-CV mode, i.e. a constant current (CC) of 0.05 C was applied, followed by a constant voltage (CV) hold at 4.3 V until 0.02 C was reached. After resting for 5 min, re-lithiation was performed at a constant current of 0.05 C to 2.7 V. For the cycles, the current density was C / 3. Results are summarized in Table 2.
[0253] Single layer pouch battery cells were tested after several formation cycles at C / 3 over a voltage range between 4.2 and 2.85 V.
[0254] Table 2: Single layer pouch battery cell performance (40 °C cycling)
[0255]
[0256] Between 20% and 45% of the particles of CAM.1 exhibited cracks after 500 cycles as determined by SEM imaging. More than 45% of the particles of C-CAM.2 exhibited cracks after 500 cycles.
Claims
1. A cathode active material comprising (A) According to the general formula Li 1+x TM 1-x A core material of O2, wherein TM is a combination of Ni and at least two of Mn, Co and Al, and optionally at least one metal selected from Mg, Ti, Zr, Nb, Ta and W, and x is in the range of -0.05 to +0.05, and wherein the nickel content is in the range of 80 to 99 mol-% of TM, and (B) Particles of one or more cobalt compounds, wherein at least some of the cobalt is in the +III oxidation state and is selected from Li y1 CoO2, LiCoO2 and LiCo y2 Ni 1-y2 O2, where 0 < y1 < 0.6 and 0.5 < y2 < 1, (C) a shell comprising at least one compound selected from B2O3, WO3, LiBO2, Li2B4O7 and Li2WO4, The core material (A) is a polycrystalline material, the secondary particles of the polycrystalline material are composed of primary particles, and the particles (B) of the cobalt compound are enriched at the surfaces of the secondary particles.
2. The cathode active material according to claim 1, wherein TM is a combination of transition metals according to formula (I) (Ni a Co b Mr c ) 1-d M d (I) in a is in the range of 0.80 to 0.99, b is in the range of 0.005 to 0.12, c is in the range of 0.005 to 0.12, and d is in the range of 0 to 0.1, M is selected from Al, Mg, Ti, Zr, Nb, Ta and W, and a+b+c=1.
3. The cathode active material according to claim 1 or 2, wherein The coating comprises LiCoO2.
4. The cathode active material according to any one of the preceding claims, wherein Between 20% and 45% of these secondary particles exhibited cracks in full cells with graphite anodes after 500 cycles of charge / discharge at 4.2-3.0 V at 40°C.
5. The cathode active material according to any one of the preceding claims, wherein These particles (B) have an average diameter (D50) in the range from 10 nm to 1 μm, but in any case smaller than the diameter of the core (A), when the average particle size (D50) is determined by SEM or TEM.
6. A method for producing a cathode active material according to any one of the preceding claims, the method comprising the following steps: (a) providing an oxide or (oxy)hydroxide of TM, wherein TM is a combination of Ni and at least two of Mn, Co and Al, and optionally at least one metal selected from Mg, Ti, Zr, Nb, Ta and W, and wherein the nickel content is in the range of 80 to 99 mol-% of TM, (b) mixing said oxide or (oxy)hydroxide with an oxide or (oxy)hydroxide of cobalt selected from CoO, Co3O4, Co(OH)2, CoOOH and a non-stoichiometric oxyhydroxide of cobalt, and optionally at least one oxide or (oxy)hydroxide of Al, Nb, Ti or Zr, thereby obtaining a premix, (c) adding a lithium source to the premix obtained in step (b) at a molar ratio of Li to TM in the range of (1+x+y) / (1-x), wherein x is in the range of 0 to 0.05, and y is in the range of 0 to 0.1, thereby obtaining a mixture, and (d) calcining the mixture of step (c), (e) at least one post-processing step selected from the group consisting of (e1) treating the calcined material from step (d) with water, followed by a liquid-solid separation step, and (e2) adding a compound of B or W to the calcined material of step (d) or to the treated material from step (e1) and performing a heat treatment at a temperature in the range of 250°C to 400°C, wherein the compound of B is selected from B2O3, boric acid (B(OH)3) and lithium borate, and the compound of W is selected from WO3, (NH4)2WO4, Li2WO4 and Li4WO5.
7. The method according to claim 6, wherein: Step (d) is performed at a temperature in the range of 550°C to 800°C.
8. The method according to claim 6 or 7, wherein: In step (a) an oxide of TM is provided having a moisture content in the range of 0 to 100 ppm as determined by Karl-Fischer titration.
9. The method according to any one of claims 6 to 8, wherein Steps (b) and (c) are carried out in different mixer types.
10. The method according to any one of claims 6 to 9, wherein Step (b) is carried out in a dry state.
11. The method according to any one of claims 6 to 10, wherein TM is a combination of metals according to formula (I) (Ni a Co b Mr c ) 1-d M d (I) in a is in the range of 0.80 to 0.99, b is in the range of 0.005 to 0.12, c is in the range of 0.005 to 0.12, and d is in the range of 0 to 0.1, M is selected from Al, Mg, Ti, Zr, Nb, Ta and W, and a+b+c=1.
12. An electrode comprising (A) at least one cathode active material according to any one of claims 1 to 5, (B) carbon in an electrically conductive form, and (C) Adhesive.
13. A secondary battery comprising (1) at least one electrode according to claim 12, (2) at least one anode, and (3) Electrolytes.
Citation Information
Patent Citations
Gradient cathode material for lithium rechargeable batteries
US6921609B2
